A Single Session of Repetitive Transcranial Magnetic Stimulation Over the Dorsolateral Prefrontal Cortex in Patients With Unresponsive Wakefulness Syndrome: Preliminary Results. (August 2015) - Naro, Antonino; Russo, Margherita; Leo, Antonino; Bramanti, Placido; Quartarone, Angelo; Calabrò, Rocco Salvatore
Background . The level of consciousness is regulated by the activation of the frontal parietal network since a disruption within this interregional cortical connectivity is associated with a consciousness breakdown. Objective . The primary aim of the present study was to examine the feasibility and the safety of a single session of repetitive transcranial magnetic stimulation (rTMS), delivered over the dorsolateral prefrontal cortex (DLPFC), in patients with unresponsive wakefulness syndrome (UWS). As a secondary aim, we investigated the efficacy of rTMS over DLPFC on cortico-cortical connectivity as tested with paired-pulse and dual-coil TMS techniques. Methods . We enrolled 10 healthy and 10 postanoxic UWS subjects. After clinical assessment, subjects underwent a single/paired pulse TMS paradigm evaluating the inhibitory and facilitatory intracortical circuits. In addition, several interregional interactions between primary motor, dorsal and ventral premotor, supplementary motor, and posterior parietal cortex areas were investigated by means of dual-coil TMS technique. These parameters were evaluated at baseline, immediately after, and 60 minutes after a protocol of 10-Hz rTMS delivered at the level of the DLPFC. Results . rTMS over DLPFC did not cause any adverse events. We showed that rTMS over DLPFC did not induce, at group level, any clinical improvement or intra-/intercortical connectivity changes. Interestingly, in 3 patients rTMS induced a significant, although transient, clinical improvement associated with a short-lasting reshaping of brain connectivity. Conclusions . We demonstrated that a single session of 10-Hz rTMS over the right DLPFC may transiently improve consciousness and partially restore the connectivity within several cortical areas in some patients with UWS.